PENGARUH ASPEK PELAKSANAAN KONSTRUKSI TERHADAP KINERJA WAKTU PROYEK (STUDI KASUS DI DINAS CIPTA KARYA DAN TATA RUANG PROVINSI JAWA TENGAH) - Hartono, Hartono; Lukman, Lukman (Diponegoro University, 2013)
At execution process of a project of construction of building development, start from idea of up to finishing of aproject, will always influenced by previous activity, that is start from idea and planning which have beenplanned, as its execution guidance. process the the execution, will be related/relevant always with the expense,time and quality from itself construction. For that presumably require to perform of research for the problem ofexecution time of a project.This research target is to know the relation among execution of construction project to performance of projectexpense, and performance of project time. This research is expected by be of benefit to serve service, and directrelated other party with the project organizer, so that project performance of below On duty Create theMasterpiece and Planology of Province of Central Java and improved later on day.From data analysis obtained.:Make-Up of amount and appliance condition used for the work of especial,execution method work, and draw the execution, will improve the time performance.